Assessment of Fluoride Level in Drinking Water Sources of Jumla, Nepal - Poudel, Kabiraj; Subedi, Sudeep; Banskota, Merika; Timalsina, Bishow Raj; Bhattarai, Kushal; Thapa, Nabin (Journal of Nepalese Association of Pediatric Dentistry, 2022)
Introduction: Dental caries is one of the most prevalent chronic diseases. Though, preventable recent trend shows an increase in the prevalence of dental caries in developing country like Nepal. Optimal level of Fluoride in drinking water has a proven effect of preventing dental caries. Objective: The objective of this study was to estimate the amount of fluoride in drinking water of Jumla, Nepal. Methods: This study was an observational cross-sectional study conducted from August to September 2022 during which 78 drinking water samples were collected from different randomly selected wards of one municipality and seven rural municipality of Jumla district using simple random sampling technique. The drinking water sample for fluoride level of different area was analyzed and interpreted using SPADNS colorimetric method which is set as standard by American Public Health Association. Results: A total of 78 samples were collected from distinctive drinking water sources of randomly selected wards of 7 rural municipality and a municipality. Out of 78 samples collected, only 5 samples (6.41%) had a fluoride concentration of more than 0.5mg/L. The highest fluoride concentration was 1.31mg/L. The overall mean (±SD) fluoride concentration of Jumla district was 0.20(±0.24). The median (Q1-Q3) concentration of fluoride in drinking water of Jumla district was estimated to be 0.11mg/L (0.05-0.29). Conclusions: This study estimated the fluoride level in drinking water of Jumla district to be below the optimal level and shows the importance of water fluoridation in order to prevent dental caries.